PENGARUH PELAKSANAAN PELATIHAN KARYAWAN TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PT JAMSOSTEK KANTOR WILAYAH VIII MAKASSAR - Sukardi Sukardi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
This study aims to determine how to influence the implementation of employee training on PT Jamsostek (Persero) Region VIII Office of Makassar and find out what the obstacles faced in the implementation of employee training in PT Jamsostek (Persero) Region VIII Office of Makassar. Data collection techniques used were: questionnaires, the data collection techniques through questionnaires filled out by respondents' own interview, which is a technique of collecting data through direct questioning by informants that existed at the company in order to obtain the information needed. The results showed that the process of conducting training in PT Jamsostek (Persero) Region VIII Office of Makassar executed well, and has a significant influence on employee performance penigkatan, but still needs to be improved